Nonrenewable Resources, Strategic Behavior and the Hotelling Rule: An Experiment - Roel van Veldhuizen; Joep Sonnemans (Tinbergen Institute, 2011)
This study uses the methods of experimental economics to investigate possible causes for the failure of the Hotelling rule for nonrenewable resources. We argue that as long as resource stocks are high enough, producers may choose to (partially) ignore the dynamic component of their production decision, shifting production to the present and focusing more on strategic behavior. We experimentally vary stock size in a nonrenewable resource duopoly setting and find that producers with high stocks indeed pay significantly less attention to variables related to dynamic optimization, leading to a failure of the Hotelling rule.
Keywords: C90; Q31; Q41; L13; 330; Experiments; Nonrenewable Resources; Dynamic Oligopoly; Erschöpfbare Ressourcen; Oligopol; Hotelling-Regel; Experimentelle Ökonomik; Theorie